2012
DOI: 10.1007/s00418-012-1032-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased caveolae density and caveolin-1 expression accompany impaired NO-mediated vasorelaxation in diet-induced obesity

Abstract: Diet-induced obesity induces changes in mechanisms that are essential for the regulation of normal artery function, and in particular the function of the vascular endothelium. Using a rodent model that reflects the characteristics of human dietary obesity, in the rat saphenous artery we have previously demonstrated that endothelium-dependent vasodilation shifts from an entirely nitric oxide (NO)-mediated mechanism to one involving upregulation of myoendothelial gap junctions and intermediate conductance calciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 83 publications
0
29
0
Order By: Relevance
“…By contrast, cav-3 is the only isoform expressed in cardiomyocytes, visceral-smooth muscle and skeletal muscle cells. 4, 5 These specialized regions act to reduce the fluidity of the plasma membranes that they segregate. 6 Using transmission electron microscopy, we show in Figure 1 the overall shape and location of caveolae in ovine uterine artery endothelial cells (UAECs) and are identified by the arrows.…”
Section: Caveolae and Their Role In Trafficking Of Enosmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, cav-3 is the only isoform expressed in cardiomyocytes, visceral-smooth muscle and skeletal muscle cells. 4, 5 These specialized regions act to reduce the fluidity of the plasma membranes that they segregate. 6 Using transmission electron microscopy, we show in Figure 1 the overall shape and location of caveolae in ovine uterine artery endothelial cells (UAECs) and are identified by the arrows.…”
Section: Caveolae and Their Role In Trafficking Of Enosmentioning
confidence: 99%
“…Studies that utilized an over-expression of cav-1 have showed a reduced basal NO production in a “control” cellular state, cav-1 interaction with eNOS has been shown to negatively regulate NO release. 4 It has been established that eNOS requires palmitoylation and myristoylation in order to be targeted to the caveolae microdomains. Upon agonist activation, (e.g.…”
Section: Caveolae and Their Role In Trafficking Of Enosmentioning
confidence: 99%
“…Interestingly, control endothelial cells were not programmed for altered protein expression upon ATP treatment. Over-expression of cav-1 leads to decreased NO production and cav-1 interaction with eNOS negatively regulates basal NO release [33]. Thus, eNOS and cav-1 are significant targets of chronic alcohol exposure [34-36] in the umbilical vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the microcirculation (cremaster muscle arterioles) of diet-induced obese rats, endothelial caveolae density is decreased, which leads to improved NOS3 function and sGC-dependent vasodilation [17]. In contrast, in saphenous arteries from obese rats, increased endothelial caveolae density and caveolin-1 expression levels are associated with inhibition of NOS3 activity and impaired vasorelaxation [18]. These seemingly conflicting results most likely reflect vascular bed-specific modulation of caveolins in response to obesity.…”
Section: No/sgc In Vascular Dysfunctionmentioning
confidence: 99%